2020
DOI: 10.1002/cche.10310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic stress on bioactive compound production in germinated brown rice

Abstract: Background and objectivesThe objective of this study was to evaluate the effect of germination and various abiotic stresses on the technological, nutritional, and sensorial characteristics of brown rice. The seeds were soaked at 40°C and 30% humidity. The soaked seeds were allowed to germinate at 30°C for 36 hr in BOD chamber. The soaked rice grains were subjected to stress conditions in the last 4 hr of germination using saline (SBR/S), low temperature (4°C) (SBR/C), or a combination of saline and low tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Among all treatments, B2 showed the highest antiradical activities against DPPH and ABTS (IC 50 = 1.58 and 1.78 mg/mL, respectively) compared to others. Several studies have consistently demonstrated that different germination conditions and salt stress enhanced the antioxidant capacity of GBR [ 6 , 56 , 57 ]. This result may be due to the upregulation of relevant enzymes such as superoxide dismutase, catalase, glutathione peroxidase, and ascorbate peroxidase in rice under abiotic stresses [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among all treatments, B2 showed the highest antiradical activities against DPPH and ABTS (IC 50 = 1.58 and 1.78 mg/mL, respectively) compared to others. Several studies have consistently demonstrated that different germination conditions and salt stress enhanced the antioxidant capacity of GBR [ 6 , 56 , 57 ]. This result may be due to the upregulation of relevant enzymes such as superoxide dismutase, catalase, glutathione peroxidase, and ascorbate peroxidase in rice under abiotic stresses [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, enzymatic activities during seed germination modify the bioactive substances through interactions between proteins and carbohydrates in the grain endosperm [ 4 , 5 ]. Accordingly, GBR has been reported to have a proliferation of bio-functional constituents such as γ-aminobutyric acid (GABA) [ 1 , 6 ], vitamins, and amino acids [ 7 ], as well as a reduction of sugar [ 8 ], compared to non-GBR. On the other hand, previous studies indicated that subjecting germinated brown rice (GBR) to abiotic stresses and various germination conditions can lead to improved nutritional profiles and an elevated accumulation of bioactive compounds and antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GBR is one of the plant foods rich in GABA and serves as the main raw material for the development of GABA functional foods (Shu et al, 2008). According to previous reports, GABA synthesis may be elevated by environmental stresses (Nascimento et al, 2020;Poojary et al, 2017), including mechanical and environmental stimuli such as hypoxia, darkness, visible light, ultraviolet light, heat shock, cold shock, and cytosolic acidification (Wang et al, 2019;Xia et al, 2018). In general, stressful conditions increase cytosolic Ca 2+ , calmodulin, or H + levels, leading to a reduction in cytosolic pH and subsequently to increased GAD activity (Komatsuzaki et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is used as a food source and a medical therapy in many countries. The improvement of bioactive compounds in rice through biotic and abiotic stress has been studied previously ( Nascimento et al, 2020 ; Katiyar et al, 2022 ). The most common abiotic stresses used to promote the synthesis of bioactive compounds in rice include gamma radiation and salt, flooding, and drought stress ( Dash et al, 2018 ; Chinvongamorn and Sansenya, 2020 ; Panda and Barik, 2021 ).…”
Section: Introductionmentioning
confidence: 99%